Salsalate reverses metabolic disorders in a mouse model of non‐alcoholic fatty liver disease through AMPK activation and caspase‐6 activity inhibition. Issue 3 (27th November 2020) - Li, Jingjing; Chen, Changmai; Zhang, Wei; Bi, Jing'ai; Yang, Guang; Li, Erguang
Abstract: Salsalate, an ester formed by 2 salicylic acid molecules, has beneficial effect against metabolic disorders in clinical trials and in animal studies. This study focused on the mechanistic aspects of salsalate activity against non‐alcoholic fatty liver disease (NAFLD). Using high‐fat diet (HFD) fed mice, we showed that salsalate treatment decreased body‐weight gains, reduced white adipose tissue mass and improved glycaemic control. Mice in salsalate‐treated group also had reduced obese adipose tissue and hepatic macrophage infiltration and inflammation and adipogenesis gene expression. Histology analysis revealed predominant decreases in hepatosteatosis, including both macrovesicular and microvesicular steatoses. The treatment reversed AMPK activity repression that was accompanied by reduced caspase‐6 activity and cleavage. Enzymatic assay and cell culture studies showed that salsalate promoted AMPK activation by directly activating AMPK. This study links salsalate effect against metabolic disorders to its activity on reversion of AMPK repression in NAFLD mice and on suppression of adipogenic gene induction.